2021
DOI: 10.1186/s12879-021-06255-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings of Talaromyces marneffei infection among patients with anti-interferon-γ immunodeficiency: a prospective cohort study

Abstract: Background Talaromyces marneffei (T. marneffei) infection has been associated with adult-onset immunodeficiency due to anti-IFN-γ autoantibodies. We aimed to investigate the clinical features of non-HIV-infected patients with T. marneffei infection in southern China. Methods Between January 2018 and September 2020, we enrolled patients with T. marneffei infection who were HIV-negative (group TM, n = 42), including anti-IFN-γ autoantibody-positive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…The clinical characteristics reported herein were consistent with our previous findings 12 and those published previously. 10 , 11 Patients with defective T lymphocyte function due to anti-IFN-γ autoAbs tended to have severe disseminated infection and poor clinical outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The clinical characteristics reported herein were consistent with our previous findings 12 and those published previously. 10 , 11 Patients with defective T lymphocyte function due to anti-IFN-γ autoAbs tended to have severe disseminated infection and poor clinical outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…The serum anti-IFN-γ autoAb titers were determined by using an enzyme-linked immunosorbent assay kit (USCN Life Science, Inc., Wuhan, China) according to the manufacturer instructions. According to our previous study, 12 based on the 99th percentile of the anti-IFN-γ autoAb titers in 40 healthy controls, the cutoff for anti-IFN-γ autoAb positivity was 594.49 ng/mL, with higher values suggestive of higher levels of anti-IFN-γ autoAbs.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the patients with anti-IFN-g autoantibody are more likely to have pleural effusion and multiple organ involvement (23). Chen et al confirmed that patients who tested positive for anti-IFN-g autoantibody usually have more frequently exhibited disseminated systemic infections with severe pleural effusion, have stronger inflammatory responses, are more likely to be infected by other intracellular pathogen, and have worse disease outcomes despite aggressive antimicrobial therapy (71).…”
Section: Anti-ifn-g Autoantibodies In Aoidmentioning
confidence: 99%